Physical Activity and Sedentary Time: Male Perceptions in a University Work Environment - George, Emma S.; Kolt, Gregory S.; Rosenkranz, Richard R.; Guagliano, Justin M. (My University, 2013)
Promoting physical activity and reducing sedentary time in males can be challenging, and interventions tailored specifically for males are limited. Understanding male perceptions of physical activity and sedentary behavior is important to inform development of relevant interventions, especially for males working in an office setting. As part of a larger intervention study to increase physical activity and reduce sedentary time, male university employees aged 35 to 64 years were invited to partake in focus groups to discuss benefits, motivators, and barriers related to physical activity and sedentary time. Five semistructured focus group sessions, ranging from 50 to 70 minutes in duration, were conducted on two campuses at an Australian university. A total of 15 participants (9 academic/faculty staff and 6 professional staff), with a mean (± SD) age of 46.1 (±8.0) years took part in the study. Health and family were commonly discussed motivators for physical activity, whereas time constraints and work commitments were major barriers to physical activity participation. Sedentary time was a perceived “by-product” of participants’ university employment, as a substantial proportion of their days were spent sitting, primarily at a computer. Participants believed that physical activity should be recognized as a legitimate activity at work, embedded within the university culture and endorsed using a top-down approach. It is important to encourage breaks in sedentary time and recognize physical activity as a legitimate health-promoting activity that is supported and encouraged during working hours. These findings can be used as a platform from which to develop targeted strategies to promote physical activity in male university employees.
Keywords: Sedentary time; Focus groups; Middle-aged men; Workplace health promotion; Physical activity; Physical activity